2015
DOI: 10.1007/978-3-319-17121-0_35
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Mutations in the MERTK Proto-Oncogene

Abstract: Phagocytosis and elimination of shed aged photoreceptor outer segments (POS) by retinal pigment epithelial cells is crucial for photoreceptor function and survival. Genetic studies on a natural animal model of recessive retinal degeneration allowed the identification of MerTK, the gene encoding the surface receptor required for POS internalization. Following this discovery, screenings of DNA samples from patients have revealed that MERTK mutations cause retinal degenerations in humans. MERTK patients present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…It remains a mystery how such localized externalization of PtdSer, which is also seen in other cells [76], is achieved. The daily pruning of photoreceptor outer segments is very important: loss-of-function Mertk mutations severely compromise this phagocytosis, and result in inherited forms of retinitis pigmentosa, photoreceptor death, and blindness [73, 77]. …”
Section: Biological Phenomena Driven By Ptdser/tam Signalingmentioning
confidence: 99%
“…It remains a mystery how such localized externalization of PtdSer, which is also seen in other cells [76], is achieved. The daily pruning of photoreceptor outer segments is very important: loss-of-function Mertk mutations severely compromise this phagocytosis, and result in inherited forms of retinitis pigmentosa, photoreceptor death, and blindness [73, 77]. …”
Section: Biological Phenomena Driven By Ptdser/tam Signalingmentioning
confidence: 99%
“…This genetic defect is a common etiology of autosomal dominant RP (Hartong et al, 2006) and causes defective disc formation, protein misfolding, endoplasmic reticulum stress, and photoreceptor degeneration (Steinberg et al, 1996; Machida et al, 2000; Veleri et al, 2015). The RCS rat bears a mutation of a RPE specific protein: MERTK, which is a tyrosine-protein kinase MER that has been also found in humans with early onset retinal degeneration and Leber Congenital Amaurosis (Gal et al, 2000; Veleri et al, 2015; Parinot and Nandrot, 2016). In this model, photoreceptor degeneration is the result of the failure of the RPE cells to phagocytize outer segment debris (LaVail, 1981; Duncan et al, 2003; Veleri et al, 2015; Parinot and Nandrot, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The RCS rat bears a mutation of a RPE specific protein: MERTK, which is a tyrosine-protein kinase MER that has been also found in humans with early onset retinal degeneration and Leber Congenital Amaurosis (Gal et al, 2000; Veleri et al, 2015; Parinot and Nandrot, 2016). In this model, photoreceptor degeneration is the result of the failure of the RPE cells to phagocytize outer segment debris (LaVail, 1981; Duncan et al, 2003; Veleri et al, 2015; Parinot and Nandrot, 2016). In the first animal model, rods are affected first while in the second, as the defect is manifested in the RPE, both rods and cones are affected.…”
Section: Introductionmentioning
confidence: 99%
“…After these initial studies, multiple MERTK mutations were documented in patients with RP. These patients’ disease progression is thought to be more severe than typical RP cases, with early onset in the first decade of life and quickly worsening macular atrophy as seen in our family[15]. …”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors continually renew the light-sensitive disks in their outer segments as they bear significant light stress. These shed disks are phagocytized by the RPE [14, 15]. Prior studies have demonstrated that initial photoreceptor outer segment binding to RPE cells is facilitated by the αvβ5 integrin while MERTK is necessary for phagocytosis of the outer segments [1618].…”
Section: Introductionmentioning
confidence: 99%